Central Asian Gypsies - Lyuli. The overview of current socio-economic problems = Cyganie z Azji Środkowej - Lyuli. Przegląd aktualnych problemów społeczno-gospodarczych - Ozierski, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The ethnic group known by many names - calling themselves Mugat or Mugati Tubjoni, and by others as Lyuli, Jugi, Multoni, Mazang and Tavoktarosh. The paper attempt to shed light on current socio-economic problems of ethnic group popularly known in post-Soviet area as "Central Asian Gypsies", due to their regional inhabitancy in Central Asia, primarily Tajikistan, Uzbekistan and Kyrgyzstan.
Keywords: Gypsies; Lyuli; emigration; Central Asia; Cyganie; emigracja; Azja Centralna